C-Jun N-terminal kinases differentially regulate TNF- and TLRs-mediated necroptosis through their kinase-dependent and -independent activities. Issue 12 (December 2018) - Cao, Mengtao; Chen, Fei; Xie, Ni; Cao, Meng-Yao; Chen, Pengfei; Lou, Qi; Zhao, Yanli; He, Chen; Zhang, Shuyuan; Song, Xinyang; Sun, Yu; Zhu, Weimin; et al.
Abstract Tumor necrosis factor (TNF) and Toll-like receptor (TLR)3/TLR4 activation trigger necroptotic cell death through downstream signaling complex containing receptor-interacting protein kinase 1 (RIPK1), RIPK3, and pseudokinase mixed lineage kinase-domain-like (MLKL). However, the regulation of necroptotic signaling pathway is far less investigated. Here we showed that c-Jun N-terminal kinases (JNK1 and JNK2) displayed kinase-dependent and -independent functions in regulating TNF- and TLRs-mediated necroptosis. We found that RIPK1 and RIPK3 promoted cell-death-independent JNK activation in macrophages, which contributed to pro-inflammatory cytokines production. Meanwhile, blocking the kinase activity of JNK dramatically reduced TNF and TLRs-induced necroptotic cell death. Consistently, inhibition of JNK activity protected mice from TNF-induced death andStaphylococcus aureus -mediated lung damage. However, depletion of JNK protein using siRNA sensitized macrophages to necroptosis that was triggered by LPS or poly I:C but still inhibited TNF-induced necroptosis. Mechanistic studies revealed that RIPK1 recruited JNK to the necrosome complex and their kinase activity was required for necrosome formation and the phosphorylation of MLKL in TNF- and TLRs-induced necroptosis. Loss of JNK protein consistently suppressed the phosphorylation of MLKL and necrosome formation in TNF-triggered necroptosis, but differentially promoted the phosphorylation of MLKL and necrosome formation in poly I:C-triggered necroptosis by promoting the oligomeration of TRIF. In conclusion, our findings define a differential role for JNK in regulating TNF- and TLRs-mediated necroptosis by their kinase or scaffolding activities.